IMPLEMENTATION OF THINK TALK WRITE (TTW) LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN LEARNING GEOGRAPHY CLASS XI IPS 2 MA ALKHAIRAAT TONDO - lilis endang pujiati; Nur Vita; ika listiqowati (Journal Learning Geography, 2020)
The purpose of this study was to improve student learning outcomes in Geography subjects XI IPS 2 MA Alkhairaat Tondo. This research is a class action research. Each cycle consists of planning, implementing actions, observing, and reflecting. The research subjects were 18th grade students of IPS IPS 2 MA Alkhairaat Tondo. The results showed that through the Implementation of Cooperative Learning Model Think Talk Write Type can improve student learning outcomes with the acquisition of KBK 61.11% and DSK 66.11% in the first cycle, to 88.88% KBK and 77.88% DSK in the second cycle . Observation results of student activitiesthe first cycle of action I obtained 2.77% with less criteria, whereas in the first cycle of action II obtained 58.33% with sufficient criteria. The results of observing student activities in the second cycle of action I on very good criteria obtained 77.77%, while in the second cycle of action II obtained 88.88% with very good criteria. The observation results of teacher activity in the first cycle of action I obtained 50% and in the second cycle I obtained 75%. Then the results of observations of the activities of the second cycle teacher in class XI IPS 2 actions I and II are better seen from the percentage achieved between 75% to 100%. In general there is an increase in student activity and student learning outcomes in each cycle.Tujuan penelitian ini adalah untuk meningkatkan hasil belajar siswa pada mata pelajaran Geografi kelas XI IPS 2 MA Alkhairaat Tondo. Penelitian ini merupakan penelitian tindakan kelas. Tiap siklus terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas XI IPS 2 MA Alkhairaat Tondo berjumlah 18 siswa. Hasil penelitian menunjukkan bahwa melalui Implementasi Model Pembelajaran Kooperatif Tipe Think Talk Write dapat meningkatkan hasil belajar siswa dengan perolehan KBK 61,11% dan DSK 66,11% pada siklus I, menjadi 88,88% KBK dan 77,88% DSK pada siklus II. Hasil observasi aktivitas siswa siklus I tindakan I diperoleh 2,77% dengan kriteria kurang, sedangkan pada siklus I tindakan II diperoleh 58,33% dengan kriteria cukup. Hasil observasi aktivitas siswa pada siklus II tindakan I pada kriteria sangat baik diperoleh 77,77%, sedangkan pada siklus II tindakan II diperoleh 88,88% dengan kriteria sangat baik. Hasil observasi aktivitas guru pada siklus I tindakan I diperoleh 50% dan pada tindakan ke II siklus I diperoleh 75%. Kemudian pada hasil observasi aktivitas guru siklus II di kelas XI IPS 2 tindakan I dan II semakin baik dilihat dari persentase tercapai antara 75% sampai 100%. Secara umum terjadi peningkatan aktivitas siswa dan hasil belajar siswa pada setiap siklus.